The Role of Religiosity and Spirituality on Impulsive Buying - Wiwik Maryati; Sri Hartini; Gancar Candra Premananto (al-Uqud : Journal of Islamic Economics, 2021)
This article aims to analyze religiosity and spirituality's roles to prevent the impulsivity of buying. Impulse buying is an irrational, unplanned, spontaneous buying behavior aimed to seek pleasure and emotional fulfillment. The research method is a literature study of journals related to religiosity and spirituality in customer decision making. The study results concluded that several factors cause impulsive buying, such as less self-control, hedonic lifestyle, and materialism. Furthermore, there are significant roles of religiosity and spirituality in encouraging robust self-regulation to prevent impulse buying. The higher a person's religiosity and spirituality, the better they build powerful self-control for impulse buying. This research is expected to contribute research in consumer behavior with an approach of religiosity and spirituality.